2002
DOI: 10.1124/dmd.30.6.734
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure Activity Relationships for the Glucuronidation of Simple Phenols by Expressed Human UGT1A6 and UGT1A9

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:UGT1A6 and UGT1A9 have both been demonstrated to rapidly glucuronidate simple phenolic compounds. A series of simple phenols were selected and screened with both isoforms and then used as model substrates for the generation of V max and K m values. UGT1A6 showed a more restricted acceptance of phenolic substrates compared with UGT1A9. However, the affinity of UGT1A6 for these compounds exhibited higher K m values than UGT1A9, although ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 21 publications
4
34
1
Order By: Relevance
“…In our study, UGT1A6 and UGT1A9 were also effective in 7-O-glucuronidation of 6,7-DHCs. It has been reported that UGT1A6 catalyzed simple or planar phenols, and UGT1A9 showed a far greater proficiency in bulky substrate glucuronidations (Ethell et al, 2002). In this study, we also found that 4-PE, a compound with relatively large molecular size, was a weak substrate (10-fold less CL int of 4-PE in UGT1A6 than that of serotonin, a specific UGT1A6 probe) (Krishnaswamy et al, 2003) of UGT1A6, which is considered for being limited to small-size substrates.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, UGT1A6 and UGT1A9 were also effective in 7-O-glucuronidation of 6,7-DHCs. It has been reported that UGT1A6 catalyzed simple or planar phenols, and UGT1A9 showed a far greater proficiency in bulky substrate glucuronidations (Ethell et al, 2002). In this study, we also found that 4-PE, a compound with relatively large molecular size, was a weak substrate (10-fold less CL int of 4-PE in UGT1A6 than that of serotonin, a specific UGT1A6 probe) (Krishnaswamy et al, 2003) of UGT1A6, which is considered for being limited to small-size substrates.…”
Section: Discussionsupporting
confidence: 58%
“…It also should be noted that the expression of these two isoforms varies considerably; in the human liver, the expression of UGT1A9 is more pronounced than UGT1A6 in both mRNA and protein (Court et al, 2012;Harbourt et al, 2012;Fallon et al, 2013;Sato et al, 2014). Furthermore, UGT1A9 typically displays relatively higher affinity toward substrates compared with UGT1A6 (Ethell et al, 2002). The high protein level and the high catalytic efficacy of UGT1A9 implies that UGT1A9 plays an important role in glucuronidation of 6,7-DHCs in the human liver.…”
Section: Discussionmentioning
confidence: 99%
“…This established that more diverse datasets could be modelled, and in light the success of a UGT1A9 2D-QSMR developed previously for simple phenols [37], a more structurally diverse dataset of UGT1A9 substrates was assembled and their K i values determined using the same procedure as reported previously for UGT1A1 [42]. The chemical structures and K i values ( M) for the UGT1A9 dataset is shown in Fig.…”
Section: D-qsmrmentioning
confidence: 84%
“…QSMR that predict the K m and V max values for the glucuronidation of 24 simple 4-substituted phenols [37] by human UGT1A6 and UGT1A9 have also been developed. Molecular surface (MS-WHIM) and atomic descriptors (AT-WHIM) were used with a genetic function algorithm for model development.…”
Section: Human Ugt Modellingmentioning
confidence: 99%
“…Phenols are in fact known to be substrates for UGT1A9 as well as UGT1A6 [33]. Although these are not specific substrates, they have been widely used as standard measures of UGT1A enzyme activity, of which UGT1A6 is a major contributor [34,35,3].…”
mentioning
confidence: 99%